HBR's 10 must reads (Harvard Business Review Press, 2019)
We've reviewed the ideas, insights, and best practices from the past year of Harvard Business Review to keep you up-to-date on the most cutting-edge, influential thinking driving business today. With authors from Thomas H. Davenport to Michael E. Porter and company examples from Facebook to DHL, this volume brings the most current and important management conversations right to your fingertips